Evaluasi Tingkat Kecemasan Atlet Karate SMAKON Aceh Pada Tahun 2024 - Muhammad Iqram; Fachrul Azmi (Journal of Student Research, 2024)
Karate is a martial art originating from Japan that uses hands and feet as tools to release punches, kicks and stabs. Karate athletes must master many aspects, including physical, technical, tactical and mental aspects. It is necessary to understand the psychology of athletes' anxiety levels in karate sports, the impact of an athlete's inability to control anxiety can interfere with an athlete's skills. If the athlete is too anxious, psychological training needs to be done, especially for athletes who experience anxiety. These problems cause karate athletes to experience various conditions, one of which is the anxiety level of athletes during training and competition. This study aims to measure the anxiety level of SMAKON Aceh karate athletes.